Tumor suppressor function of formyl peptide receptor 1 in gastrointestinal cancers: a focus on the underlying signaling - Marotta, Maria; Liotti, Federica; Melillo, Rosa Marina; Prevete, Nella (Frontiers in Cell and Developmental Biology, 2025)
The homeostasis of a tissue such the gastrointestinal (GI) tract is of fundamental importance for human health, given its constant exposure to a wide variety of external substances. The Formyl peptide Receptor 1 (FPR1) is an innate immune receptor belonging to the FPR family, that can recognize various endogenous danger- and exogenous pathogen-associated molecules, triggering inflammation. Importantly, depending on the context and on the specific ligand, FPR1 can also stimulate inflammation resolution. Thus, FPR1 is a critical actor in GI physiopathology. Interestingly, not only FPR1 participates and is necessary for maintaining homeostasis, but it also exerts strong tumor suppressor properties in this tissue. The present review discusses the mechanisms responsible for this specific function of FPR1 in cancer of the GI tract, focusing in particular on FPR1-mediated signal transduction.